Effect of pollution by particulate iron on the morphoanatomy, histochemistry, and bioaccumulation of three mangrove plant species in Brazil - Pereira Arrivabene, Hiulana (2015)
In Brazil, some mangrove areas are subjected to air pollution by particulate iron from mining activities. However, the effect of this pollutant on mangrove plants is not well known. This study aimed to comparatively analyze the morphoanatomy, histochemistry, and iron accumulation in leaves of Avicennia schaueriana, Laguncularia racemosa, and Rhizophora mangle. Samples were collected from five mangrove sites of Espírito Santo state, each of which is exposed to different levels of particulate iron pollution. The amount of particulate material settled on the leaf surface was greater in A. schaueriana and L. racemosa, which contain salt glands. High iron concentrations were found in leaves of this species, collected from mangrove areas with high particulate iron pollution, which suggests the foliar absorption of this element. None of the samples from any of the sites showed morphological or structural damage on the leaves. Scanning electron microscopy (SEM) coupled to X-ray diffraction rendered a good method for evaluating iron on leaves surfaces. A histochemical test using Prussian blue showed to be an appropriate method to detect iron in plant tissue, however, proved to be an unsuitable method for the assessment of the iron bioaccumulation in leaves of A. schaueriana and R. mangle. So far, this study demonstrates the need of evaluating the pathway used by plants exposed to contaminated particulate matter to uptake atmospheric pollutants.